Hyperelastic, shape‐memorable, and ultra‐cell‐adhesive degradable polycaprolactone‐polyurethane copolymer for tissue regeneration - Suk‐Min Hong; Ji‐Young Yoon; Jae‐Ryung Cha; Junyong Ahn; Nandin Mandakhbayar; Jeong Hui Park; Junseop Im; Gangshi Jin; Moon‐Young Kim; Jonathan C. Knowles; Hae‐Hyoung Lee; Jung‐Hwan Lee; et al. (Wiley, 2022)
Abstract Novel polycaprolactone‐based polyurethane (PCL‐PU) copolymers with hyperelasticity, shape‐memory, and ultra‐cell‐adhesion properties are reported as clinically applicable tissue‐regenerative biomaterials. New isosorbide derivatives (propoxylated or ethoxylated ones) were developed to improve mechanical properties by enhanced reactivity in copolymer synthesis compared to the original isosorbide. Optimized PCL‐PU with propoxylated isosorbide exhibited notable mechanical performance (50 MPa tensile strength and 1150% elongation with hyperelasticity under cyclic load). The shape‐memory effect was also revealed in different forms (film, thread, and 3D scaffold) with 40%-80% recovery in tension or compression mode after plastic deformation. The ultra‐cell‐adhesive property was proven in various cell types which were reasoned to involve the heat shock protein‐mediated integrin (α5 and αV) activation, as analyzed by RNA sequencing and inhibition tests. After the tissue regenerative potential (muscle and bone) was confirmed by the myogenic and osteogenic responses in vitro, biodegradability, compatible in vivo tissue response, and healing capacity were investigated with in vivo shape‐memorable behavior. The currently exploited PCL‐PU, with its multifunctional (hyperelastic, shape‐memorable, ultra‐cell‐adhesive, and degradable) nature and biocompatibility, is considered a potential tissue‐regenerative biomaterial, especially for minimally invasive surgery that requires small incisions to approach large defects with excellent regeneration capacity.